Research on the Impact of Brand Culture on Consumer Identity - Jiang, Mengqi; Peng, Bangxin (Rajapark Journal, 2025)
With the rapid growth of globalization and informatization in the global market, consumers are exposed to an increasingly wide selection of goods and services. Consumption behavior is not only a process of satisfying functional needs, but also a means of expressing oneself and constructing identity. Thus, we aim to explore whether brand culture affects consumer recognition and examine the impact of each dimension of brand culture, including brand values, brand stories, brand attitudes, and brand communities, using a systematic analysis approach. This study also examines the mechanisms by which brand culture affects consumer recognition. Data were collected based on a survey of 436 electronic product consumers in Qingdao, China. The study's conclusion suggests that brand culture and its various dimensions can influence the level of consumer identity through the transmission of values, effective communication, and resonance with consumers, as well as the shaping of brand symbols.